Antigua and Barbuda : Public Expenditure and Financial Accountability (PEFA) Performance Assessment. (IMF Staff Country Reports; Country Report, 2015)
The purpose of this Public Expenditure and Financial Accountability (PEFA) performance assessment is to provide an objective analysis of the present performance of the public financial management system in Antigua and Barbuda, and identify changes incurred since the last PEFA assessment undertaken in 2010. In the wake of a prolonged economic crisis, fiscal outcomes have not been consistent with the budget as approved. Central government public finances are comprehensively presented in budget documents, but some weaknesses persist. New policy initiatives and their budgetary implications are not sufficiently analyzed; a significant share of extra-budgetary expenditures remains unreported; and oversight and reporting requirements of statutory bodies are not yet fully enforced, impeding a comprehensive assessment of the associated fiscal risks. Although the revenue administration has been strengthened over the last years, the control over budget execution is still weak. There have been improvements in the quality of external audit, but lack of Parliamentary scrutiny undermines the accountability framework.